Junior High School Student's Perception of Using Dictogloss for Their Listening Ability - Ghoniya, Indah Rima Rachmawati (RETAIN : Journal of Research in English Language Teaching, 2024)
This study aims to determine the increase in learning outcomes of listening and perceptions or opinions of students in class VIII-K SMPN 35 Surabaya on the Dictogloss technique. The author uses data collection methods by testing and observation to get the results of increasing listening and perceptions or opinions of class VIII-K SMPN 35 Surabaya on the Dictogloss technique to improve listening skills. The research findings show that there is a significant increase in learning listening to material in class VIII-K SMPN 35 Surabaya when students get the dictogloss technique.